Factors Associated To The Hemoglobin Reduction In Postpartum Women Treated At The Maternal Perinatal National Institute-2012 - Díaz-Tinoco, Clara (2016)
Objective. To analyze the factors that are associated with reduced hemoglobin levels in postpartum women treated at the National Maternal and Perinatal Institute during 2012. Materials and methods. Case-control study where 274 patients divided in 137 postpartum women with hemoglobin difference 1.3 g / di (cases) and 137 with a difference of hemoglobin <1.3 g / di (controls). Descriptive and inferential statistics, measures of central tendency and dispersion for quantitative variables, frequency distribution for qualitative variables for statistical inferences applied Chi-square, OR 95% CI and binary logistic regression for multivariate analysis was applied.